Hak Perempuan dalam Islam: Tantangan Antara Prinsip HAM dan Budaya Patriarki - Human Rights; Uswatun Hasanah (Pusat Riset dan Inovasi Nasional, 2025)
Human rights and Islam both emphasize the value of justice and well-being for all individuals, including women. However, in practice, women's rights are often hampered by patriarchal culture and conservative religious interpretations. This study aims to analyze how human rights and Islam can work in harmony in guaranteeing women's rights. Using a qualitative method based on literature study, this research identifies various factors that cause discrimination against women, such as gender bias in religious interpretations and entrenched social norms. The results show that realizing gender equality in Islam requires inclusive education, fairer reinterpretation of Islamic law, policy reforms that protect women, as well as economic empowerment and women's participation in leadership. With these steps, women can obtain their full rights without erroneous cultural and religious barriers.